2007
DOI: 10.1248/cpb.55.1342
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Flowers. XVII. New Dammarane-Type Triterpene Glycosides from Flower Buds of American Ginseng, Panax quinquefolium L.

Abstract: The Araliaceae plant, Panax (P.) quinquefolium L., which is called as American ginseng or North American ginseng, is widely cultivated in U.S.A., Canada, and China. The roots of this plant are used for the same medicinal purposes as Ginseng, the roots of P. ginseng C. A. MEYER. The biologically active constituents of the roots have been pursued extensively and many dammarane-type triterpene oligoglycosides have been characterized as the principal ingredients.2-6) On the other hand, the flower buds of P. quinqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 29 publications
(48 reference statements)
0
50
0
Order By: Relevance
“…Subsequently, in continuation of our research on P. ginseng, 6,7 the present study on chemical components of the steamed flower-buds led to the isolation of one new damarane-type saponin, named ginsenoside SF (1) (Fig. 1), and nineteen known saponins (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) (Fig. 2), including ginsenoside Rh4 (2), 8 ginsenoside Rk3 (3), 8 ginsenoside F1 (4), 9 (20E)-ginsenoside F4 (5), 10 ginsenoside Rg2 (6), pseudoginsenoside RC1 (7), 4 ginsenoside Rg6 (8), 12 ginsenoside F4 (9), 12 ginsenoside Rg1 (10), 13 6'-acetyl-ginsenoside Rg1 (11), 14 ginsenoside Rd (12), 6 ginsenoside Rc (13), 6 ginsenoside Rb 2 (14), 6 ginsenoside Re (15), 6 vinaginsenoside R4 (16), 6 ginsenoside Mb (17), 15 ginsenoside Rb1 (18), 6 ginsenoside Rs4 (19), 16 and 6'-acetyl-ginsenoside F1 (20), 14 respectively, on the basis of NMR, ESI-MS data, and comparison with those reported in the literature.…”
Section: -4mentioning
confidence: 62%
“…Subsequently, in continuation of our research on P. ginseng, 6,7 the present study on chemical components of the steamed flower-buds led to the isolation of one new damarane-type saponin, named ginsenoside SF (1) (Fig. 1), and nineteen known saponins (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) (Fig. 2), including ginsenoside Rh4 (2), 8 ginsenoside Rk3 (3), 8 ginsenoside F1 (4), 9 (20E)-ginsenoside F4 (5), 10 ginsenoside Rg2 (6), pseudoginsenoside RC1 (7), 4 ginsenoside Rg6 (8), 12 ginsenoside F4 (9), 12 ginsenoside Rg1 (10), 13 6'-acetyl-ginsenoside Rg1 (11), 14 ginsenoside Rd (12), 6 ginsenoside Rc (13), 6 ginsenoside Rb 2 (14), 6 ginsenoside Re (15), 6 vinaginsenoside R4 (16), 6 ginsenoside Mb (17), 15 ginsenoside Rb1 (18), 6 ginsenoside Rs4 (19), 16 and 6'-acetyl-ginsenoside F1 (20), 14 respectively, on the basis of NMR, ESI-MS data, and comparison with those reported in the literature.…”
Section: -4mentioning
confidence: 62%
“…10,11) Furthermore, those oligoglycosides were found to exhibit antiallergic, 6) antidiabetic, 7) antiobesitic, 5,8) gastroprotective, 7,10,11) and platelet aggregation 10,11) activities. In the course of our characterization studies on Camellia speicies [12][13][14][15] and medicinal flowers, [16][17][18][19][20][21] we found that the methanolic (MeOH) extract and its 1-butanol (1-BuOH)-soluble fraction from the flower buds of C. oleifera showed gastroprotective effects on ethanol-or indomethacin-induced gastric mucosal lesions in rats. The 1-BuOH-and ethyl acetate (EtOAc)-soluble fractions exhibited inhibitory activities on rat lens aldose reductase and scavenging effects on 1,1-diphenylpicryl-2-hydrazyl (DPPH) radical and superoxide.…”
mentioning
confidence: 99%
“…It has been shown that ginsenosides are the most effective agents in the treatment and prevention of cancer in ginseng. More than 60 different types of ginseng have been identified (Nakamura et al, 2007;Qu et al, 2009). that are in different parts of the plant including roots, leaves and fruits.…”
Section: About Ginsengmentioning
confidence: 99%